Mutations in the glnG gene of Escherichia coli that result in increased activity of nitrogen regulator I. - Weglenski, P (1989)
Mutations in the glnG gene of Escherichia coli that result in increased activity of nitrogen regulator I (NRI), the product of glnG, were obtained by two different selection procedures. The mutant proteins were purified and characterized. The concentrations of mutant proteins needed to activate transcription at the glnAp2 promoter were three to four times lower than that of the wild-type NRI. The rate of phosphorylation of these proteins and the stability of mutant NRI phosphate were found to be similar to those of the wild-type NRI. In one of the mutants, the site of the mutation was localized in the DNA region specifying the central domain of NRI.